Historical construction and perception of the territory: A diachronic vision of Valladolid's landscape and its surroundings (Ciudades, 2018)
In the inventories –or environmental studies– common to the first phase of any territorial plan there’s usually included the epigraph «landscape». In some cases it appears as the culmination of the physical or natural environment, ignoring the decisive role that human societies have on the configuration of landscape and failing, therefore, in its characterization. In other cases, landscape is simply conceived as a visual picture or a scenic ensemble.
Keywords: Valladolid; diachronic; perception; landscape